3D‐Printable Denture Base Resin Containing SiO2 Nanoparticles: An In Vitro Analysis of Mechanical and Surface Properties. Issue 9 (3rd February 2022) - Gad, Mohammed M.; Al‐Harbi, Fahad A.; Akhtar, Sultan; Fouda, Shaimaa M.
Abstract: Purpose: To evaluate the flexural strength (FS), impact strength (IS), surface roughness (Ra), and hardness of 3D‐printed resin incorporating silicon dioxide nanoparticles (SNPs). Materials and Methods: A total of 320 acrylic specimens were fabricated with different dimensions according to test specifications and divided into a control group of heat denture base resin, and 3 test groups (80/test (n = 10) of unmodified, 0.25 wt%, and 0.5 wt% SNPs modified 3D‐printed resin. 10, 000 thermal cycles were performed to half of the fabricated specimens. FS, IS (Charpy impact), Ra, and hardness were evaluated and the collected data was analyzed with ANOVA followed by Tukey's post hoc test (α = 0.05). Results: Incorporating SNPs into 3D‐printed resin significantly increased the FS, IS (at 0.5%) and hardness compared to unmodified 3D‐printed resin ( p < 0.001). However, the FS of pure 3D‐printed and 3D/SNP‐0.50% resin and IS of all 3D‐printed resin groups were significantly lower than the control group ( p < 0.0001). Hardness of 3D/SNP‐0.25% and 3D/SNP‐0.50% was significantly higher than control and unmodified 3D‐printed resin ( p < 0.0001), with insignificant differences between them. The Ra of all 3D‐printed resin groups were significantly higher than control group ( p < 0.001), while insignificant difference was found between 3D‐printed groups. Thermal cycling significantly reduced FS and hardness for all tested groups, while for IS the reduction was significant only in the control and 3D/SNP‐0.50% groups. Thermal cycling significantly increased Ra of the control group and unmodified 3D‐printed resin ( p < 0.001). Conclusion: The addition of SNPs to 3D‐printed denture base resin improved its mechanical properties while Ra was not significantly altered. Thermal cycling adversely affected tested properties, except IS of unmodified 3D‐printed resin and 3D/SNP‐0.25%, and Ra of modified 3D‐printed resin.